Tracing molecular electronic excitation dynamics in real time and space - Dutoi, Anthony; Cederbaum, Lorenz S.; Wormit, Michael; Starcke, Jan Hendrik; Dreuw, Andreas (The journal of chemical physics, 2010)
We present a method for studying the movement of electrons and energy within and between electronically excited molecules. The dynamically changing state is a many-electron wavepacket, for which we numerically integrate the Schrödinger equation using the ADC(2) effective Hamiltonian for the particle-hole propagator. We develop the tools necessary for following the separate motions of the particles and holes. Total particle and hole densities can be used to give an overview of the dynamics, which can be atomically decomposed in a Mulliken fashion, or individual particle and hole states give a more detailed look at the structure of an excitation. We apply our model to a neon chain, as an illustrative example, projecting an excited eigenstate of an isolated atom onto the coupled system as the initial state. In addition to demonstrating our propagation and analysis machinery, the results show a dramatic difference in excitation-energy transfer rates as a consequence of initial polarization. Furthermore, already in a system with three constituents, an important aspect of multiple coupled systems appears, in that one absorbing system essentially shields another, changing the effective sitewise coupling parameters.
Gesehen am 20.02.2023